A Mathematical Model for Sustainable Urban Planning (Architecture Image Studies, 2025)
Delhi has undergone rapid urbanization over the past three decades, transforming vast areas of vegetation, agricultural land, and open spaces into built-up urban fabric. During this period Delhi’s air pollution has worsened dramatically: for example, modeled annual PM 2.5 levels rose by ~40% from 1998 to 2020, and recent reports identify New Delhi as the world’s most polluted capital. In this study we have observed how the land of Delhi is utilized in different categories – water bodies, vegetation, forest, agriculture, built-up areas, and open land – related to long-term air quality trends in Delhi. Using satellite-derived land cover data and annual pollution records (e.g. PM 2.5 concentrations), we have applied correlation and regression techniques to quantify the influence of each land use type on ambient pollution levels over 1991–2021.